Culturally programmed space of nursery – where we are going? - Marta Śliwa; Marzenna Nowicka (Problemy Wczesnej Edukacji)
The arrangement of the physical space of the nursery is culturally conditioned and is a very important element that influences the child development. The social functioning of children is being shaped directly by the type and origin of the elements present in kindergarten space, their arrangement, diversity and availability of different materials. Background of the research presented in the text refers to the theoretical perspective of the pedagogy of space, which emphasizes the role of the dialectical relationship between man and space in the formation of individual identity and the development of social relations. The method of visual ethnography and photographic documentation techniques supported by interviews with teachers of kindergarten were used in the study. The study included 9 kindergartens from Poland, Lithuania and the UK. The basic conclusion that emerges from the analysis of the accumulated body of research indicates that the spatial arrangement of kindergartens in post-communist countries still induces/ predisposes to the development of mirror identity operating efficiently under authoritarian rule. This kind of the interior arrangement reflects the conservative tendency to subordinate children and persistently correct their imperfections. Such a situation equals cultural look back, not forward – toward preparing children for a conscious and creative participation in society. Space of English nurseries promotes children’s autonomy and selfdetermination.